A Base‐ and Metal‐free Protocol for the Synthesis of 2‐Aryl/heteroaryl Thiazolines. Issue 2 (13th January 2017) - Chaudhary, Shweta; Milton, Marilyn D.; Garg, Parul
Abstract: A simple and efficient base‐ and metal‐ free protocol for the synthesis of 2‐aryl/heteroarylthiazoline from aryl/heteroaryl nitriles and cysteamine hydrochloride is reported. This method is applicable to a series of aryl/heteroaryl nitriles containing different substituents such as halides, amines, substituted azoles, etc. and furnishes the corresponding thiazolines in upto 99% yields. A selective synthesis of mono‐ or bis‐thiazoline in more than 90% yield was also observed by modifying the duration of the reaction. This novel methodology has been utilized for the synthesis of some important 2‐aryl/heteroarylthiazoline scaffolds which form a part of many biologically active molecules. A probable reaction mechanism involving the formation of highly activated arylimino chloride is also given. Abstract : Biologically important 2‐aryl/heteroarylthiazoline scaffolds were synthesized in good to excellent yields under base‐ and metal‐free conditions by direct condensation of aryl/heteroarylnitriles with cysteamine hydrochloride. This method is applicable to a series of aryl/heteroaryl nitriles containing different substituents such as halides, amines, substituted azoles, etc. Plausible reaction mechanism involves the formation of highly activated arylimino chloride through insitu protonation of arylnitrile by cysteamine hydrochloride.